Strategic human resources development at the National University of San Marcos - Narciso Gómez, Kennedy (2017)
The field of strategic human resource development focuses on two steps. First it is considered strategic planning; and second the strategic development of human resources. In the first step, we consider strategic thinking adapted from Michael Porter as business management tool will enable the incorporation of the processes involved in the daily life of the University with the direct participation of the Faculties and Headquarters Line in the strategic planning process with all the benefits it can bring the application of their knowledge and experience firsthand the overall performance of the University. (Porter, 1982, 1987, 1990, 1992).The main objective of the research is to formulate a plan of strategic development of human resources of the National University of San Marcos; in this first step we develop the diagnosis of external forces (economic, political, technological, cultural, social and demographic), levels of the business environment (industry, national, international), industry analysis (model 5 Competitive Forces) , internal analysis (value chain); the strategic process (formulation, implementation, control). We have considered 3 stages to the Framework Strategy Formulation: First step: Data Entry (Evaluation Matrix Matrix internal factors external factors evaluation matrix competitive profile..). Second stage: Stage comparative (SWOT Matrix Weaknesses, opportunities, strengths, threats). Third stage: Stage of decisions (quantitative strategic planning matrix). In the second step we proceeded to develop the Model of Strategic Development of Human Resources, considering the vision, mission, goals, policies, objectives, identifying the categories of strategic decisions in the area of Human Resources, Strategic Action Program. Finally, we consider investing in the Strategic Development of Human Resources of San Marcos, which will enable the success of its strategy to achieve its mission.